ANALISIS LITERASI MATEMATIS KEISLAMAN MAHASISWA TADRIS MATEMATIKA DITINJAU DARI TIPE KEPRIBADIAN KEIRSEY - Zuraidah Zuraidah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
This study aims to determine the relationship between Islamic mathematical literacy level and Keirsey personality type (Artisan, Idealist, Guardian, and Rational) in prospective mathematics teacher students, Teacher Training Faculty of IAIN Kediri. In addition, this study also aims to describe the Islamic mathematical literacy ability of prospective mathematics teacher students at the Teacher Training Faculty of IAIN Kediri, in terms of Keirsey's personality type. This research design uses a mixed-methods approach. In the quantitative approach, the type of research is correlational with a total sample of 151 students. While in the qualitative approach, the respondents used were 4 students who represented each Keirsey personality type. Sampling technique in the form of purposive sampling. There is no relationship between the level of mathematical literacy with Keirsey's personality type in prospective mathematics teacher students at the Teacher Training Faculty of IAIN Kediri. The correlation between personality type and the level of Islamic mathematical literacy of prospective mathematics teachers at IAIN Kediri was obtained with a significance of 0.22986. This means that the strength of the relationship between the two variables is included in the weak category. In the process of formulating context mathematically, there is no difference between research subjects in all personality types. All subjects can formulate context, understand, and translate problems into mathematical language or appropriate representations. In the process of using concepts, facts, procedures, and reasoning, the findings show that subjects with rational personality types are able to determine strategically in the use of mathematical concepts and are successful compared to other personality types. In the process of interpreting, applying, and evaluating the results, the findings show that subjects with rational and idealistic personality types can check the reasonableness of the solution. Meanwhile, in the artisan and guardian types, the contrary happens.